A Non‐Destructive Electrical Assay of Stem Cell Differentiation Based on Semiconductor Biosensing. Issue 2 (7th October 2022) - Hideshima, Sho; Hayashi, Hiroki; Saito, Sayoko; Tateno, Hiroaki; Momma, Toshiyuki; Osaka, Tetsuya
Abstract: Cell‐replacement therapies using human induced pluripotent stem cells (hiPSCs) with self‐renewal and pluripotency characteristics have attracted much attention in regenerative medicine. However, since residual undifferentiated cells can form tumors in transplant recipients, the deterioration of their safety after implantation needs to be resolved. In the present investigation, we developed a non‐destructive method to monitor stem cell differentiation by electrically detecting the glycoprotein biomarker podocalyxin, which is secreted from hiPSCs into cell culture supernatants using field‐effect transistor (FET) biosensors. By functionalizing the FET surface with a lectin with the small molecular size, rBC2LCN, which effectively uses a charge‐detectable region for FET‐based detection based on Debye length, the intrinsic charges of podocalyxin were successfully detected without the need for any labeling. Furthermore, it was demonstrated that the FETs monitored the decrease in the podocalyxin concentration in culture supernatants associated with the differentiation process. Our findings indicate that the FET‐based assay is a promising technique for the simple and rapid monitoring of the differentiation status of hiPSCs used for transplantation. Abstract : To improve the safety of human‐induced pluripotent stem cells (hiPSCs)‐derived cell therapy products, we built on the concept of FET biosensors for detecting actual hiPSCs. This study demonstrated that field‐effect transistor (FET) biosensors have the potential to rapidly inspect the differentiation status of hiPSCs in a non‐destructive manner by detecting the presence of a hiPSC‐specific biomarker in a culture medium.